Information Literacy: Utilization of Taman Budaya and Museum UPT Towards Motivation for Learning History - Latief, Juraid Abdul; Haliadi, Haliadi; Muchlis, Anna Asriani; Afni, Nur (PT. Riset Press International, 2024)
Information literacy learning is very important for teachers and students to improve understanding and skills related to digital media. Learning activities and motivation become triggers for certain behaviors and attitudes and giving a resistance orientation will lead to persistence and not giving up easily getting results. This research introduces museums to students as a learning resource and reference. This type of research is qualitative. The public is invited to participate in interviews and observations, providing information, opinions and perceptions to understand social phenomena from one's point of view. The results show the extent to which management of cultural parks and museums encourages the use of information technology to attract visitors to educational institutions. Providing detailed information about museum collections and exhibits related to historical themes can help curators of cultural parks and museums motivate students to learn more. This is useful for engineering practitioners because it assists the public in exploring museum collections through newspapers, brochures, magazines, websites of cultural parks and museums, as well as online social media.